Depression among tuberculosis patients attending a DOTS centre in a rural area of Delhi: A cross-sectional study - Umang P Salodia; Surabhi Sethi; Anita Khokhar (Wolters Kluwer Medknow Publications, 2019)
Background: Studies have shown that the prevalence of psychiatric disorders, particularly depression, is high among tuberculosis (TB) patients, and may adversely affect treatment compliance. A person suffering from TB can develop depression in due course of time owing to a number of factors, namely the long duration of treatment for TB, stigmatization faced by the patient due to the disease and lack of family support to name a few. Objectives: The present study aimed to determine the prevalence of depression and its correlates among TB patients enrolled at a Directly Observed Treatment Short-course (DOTS) center in a rural area of Delhi. Methods: The study was a DOTS center-based, cross-sectional study, among 106 patients of pulmonary and extrapulmonary TB, above 18 years of age. An interviewer-administered questionnaire in Hindi was used to collect basic sociodemographic data and the Patient Health Questionnaire (PHQ)-9 was used for detecting depression. Those with a score of 10 or more were considered to be suffering from depression. Data analysis was done using SPSS licensed version 20. Chi-square was used to test for association between qualitative variables, and a P < 0.05 was considered statistically significant. Results: A total of 106 patients participated in the study, of which 61 (57.5%) were males. The median age was 30 years (inter-quartile range 24-40 years). Depression was found to be present in 25 (23.6%) participants. A higher proportion of patients with depression were unemployed currently, and also belonged to middle or lower class (P < 0.05). Depression was not found to be associated with religion, gender, marital status, HIV status, presence of diabetes, DOTS category nor with the phase of treatment. Conclusion: Depression among TB patients is common, affecting almost one in four TB patients. Physicians and DOTS providers should have a high index of suspicion for depression when assessing TB patients.